2000
DOI: 10.1046/j.1365-3059.2000.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease development and enhanced susceptibility of wounded pepper roots to Phytophthora capsici

Abstract: Greenhouse experiments were conducted to determine disease progression of phytophthora root rot on nonwounded and wounded pepper plants (Capsicum annuum) and to determine whether susceptibility to Phytophthora capsici decreases with wound aging. Two isolates of P. capsici were used in this study, one less aggressive than the other. Trimming the roots immediately prior to inoculation with either isolate increased susceptibility significantly (P # 0´05) compared with plant roots that were not trimmed. Both isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…To date, even though cross‐protection is a long‐known phenomenon, very scarce data exist about the degree and modes of effective influence between abiotic and biotic stresses, and the range of true plant–pathogen interactions open to such influence (Anchisi, Gennari & Matta 1985; Matta 1991; Sharma et al. 1996; Adorada et al. 2000; Reymond et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, even though cross‐protection is a long‐known phenomenon, very scarce data exist about the degree and modes of effective influence between abiotic and biotic stresses, and the range of true plant–pathogen interactions open to such influence (Anchisi, Gennari & Matta 1985; Matta 1991; Sharma et al. 1996; Adorada et al. 2000; Reymond et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with the use of never‐ripe (Nr) tomato mutant plants impaired in ET perception, we addressed the role of the hormone in the modulation of basal and wound‐influenced susceptibility/resistance in the chosen pathosystems. Because Adorada et al. (2000) suggested that levels of total peroxidase (POD) activity could be partially responsible for the wound‐induced protection in the pepper/ Phytophthora capsici (Pc) interaction, we tried and further investigated POD activity in our experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…For different soil‐borne Phytophthora species penetration into host tissues occurs preferentially by a wound (Kaiser and Melendez, 1978; Biles et al ., 1993; Adorada et al ., 2000; Salas et al ., 2000; Thomidis, 2003). In the case of P. parasitica , infection does not occur without wounding of N. tabacum leaves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wound repair was also observed to occur, in that plants on which wounds were aged prior to inoculation showed less disease from P. capsici compared with freshly wound‐inoculated plants (Adorada et al. ). Our results show that injury was required to obtain infection of seedling stems by P. ramorum .…”
Section: Discussionmentioning
confidence: 99%